The Readiness Analysis of Online Learning at Undergraduate Students in Pandemic Era - Rizki Ayu Pratiwi (Universitas Sembilanbelas November Kolaka, 2021)
At the end of 2019, the emergence of COVID-19 affected all areas of life, especially education. Since there was still no certainty when this pandemic will end, online learning was an absolute necessity which must be fulfilled by all Indonesian students. This research aimed to determine the readiness of undergraduate students in online learning during the COVID-19 pandemic. This research was a qualitative research method using closed-ended questionnaires and interviews. Subject of this research were undergraduate students at University of Muhammadiyah Prof. Dr. Hamka. The results of this study show that students’ readiness were high in computer/internet self-efficacy, self-directed learning and motivation for learning, on the dimension of learner control and online communication self-efficacy students’ readiness were moderate. It can be concluded that undergraduate students at University of Muhammadiyah Prof. Dr. Hamka ready to face online learning. Furthermore, suggestions concerning the improvement of Online Learning Readiness were also discussed in this study.